2021
DOI: 10.32920/ryerson.14669130.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Syrian Refugee Crisis in Canadian Media

Abstract: This paper offers a critical analysis of Canadian media content (The Globe and Mail, Toronto Star, National Post, Huffington Post, CBC, and CTV), from September 2015 to April 2016, of the coverage of the Canadian resettlement effort of Syrian refugees, including representation of the refugees and the Canadian government and public. The analysis is informed by theories of orientalism, neocolonialism, neoliberalism, and feminism.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Although Syrian refugees entered Canada through a highly-praised sponsorship program rather than 'illegally' crossing the borders, studies of the coverage of Syrian refugees in the Canadian media have found biased depictions of the group as passive victims and potential threats and burdens. For example, Tyyskä et al (2017) identified frequent descriptions of Syrian refugees as vulnerable and lacking agency, while Syrian men were specifically highlighted as would-be terrorists in disguise. Although the tone of the coverage became softer and more humanizing after the emergence of the Kurdi photo (Wallace, 2018), another study found that in conservativeleaning newspapers, Syrian refugees were depicted as a burden on the healthcare system and housing resources, demonstrating the role of ideological stances of the news sources in their representations (Mustafa et al, 2021).…”
Section: Refugees In the Newsmentioning
confidence: 99%
“…Although Syrian refugees entered Canada through a highly-praised sponsorship program rather than 'illegally' crossing the borders, studies of the coverage of Syrian refugees in the Canadian media have found biased depictions of the group as passive victims and potential threats and burdens. For example, Tyyskä et al (2017) identified frequent descriptions of Syrian refugees as vulnerable and lacking agency, while Syrian men were specifically highlighted as would-be terrorists in disguise. Although the tone of the coverage became softer and more humanizing after the emergence of the Kurdi photo (Wallace, 2018), another study found that in conservativeleaning newspapers, Syrian refugees were depicted as a burden on the healthcare system and housing resources, demonstrating the role of ideological stances of the news sources in their representations (Mustafa et al, 2021).…”
Section: Refugees In the Newsmentioning
confidence: 99%